2020
DOI: 10.1002/ppsc.201900496
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Adaptable Nanoplatform for O2 Self‐Sufficient Chemo/Photodynamic Combination Therapy

Abstract: Malignant proliferation of tumor cells induces abnormal tissue microenvironments, leading to therapeutic resistance and poor therapeutic outcome. In this paper, manganese dioxide (MnO2) nanoshells are coated on a porphyrinic metal–organic framework of porous coordination network (PCN)‐224 for doxorubicin (DOX) loading and hyaluronic acid (HA) modification to obtain an intelligent nanoplatform of PCN@MnO2@DOX@HA (PMDH). Benefiting from the HA functionalization, PMDH prefers to accumulate in tumor sites and enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Among the metal-based materials for generating oxygen through H 2 O 2 decomposition, MnO 2 is a widely studied material [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. MnO 2 could produce oxygen and Mn 2+ at acidic pH, particularly in the presence of H 2 O 2 .…”
Section: Strategies For Modulating Tumor Hypoxia In Pdtmentioning
confidence: 99%
“…Among the metal-based materials for generating oxygen through H 2 O 2 decomposition, MnO 2 is a widely studied material [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. MnO 2 could produce oxygen and Mn 2+ at acidic pH, particularly in the presence of H 2 O 2 .…”
Section: Strategies For Modulating Tumor Hypoxia In Pdtmentioning
confidence: 99%
“…Due to the high r 2 /r 1 ratio ( > 15), the nanoparticles could be assigned as a T 2 -dominated contrast agent. Zhang et al reported on integrating Gd-doped silica nanoparticles within a MOF ZIF-8, which was loaded with chlorin e6 and doxorubicin (anticancer drug) in order to prepare an agent for drug delivery, and bimodal MR and fluorescent imaging . Moreover, the particle surface was functionalized with folic acid to enable tumor targeted delivery.…”
Section: Mofs As Contrast Agents In Mrimentioning
confidence: 99%
“…The r 1 relaxivity at pH 6.5 in the presence of H 2 O 2 was determined to be 6.59 mM –1 s –1 (at 1.5 T). In another work, porphyrin-based MOF nanoparticles coated with a MnO 2 shell were used for drug delivery of doxorubicin and T 1 -MRI . MR imaging of nanoparticles treated with GSH or incubated in buffer solutions with different pH values was performed.…”
Section: Mofs As Contrast Agents In Mrimentioning
confidence: 99%
“…To further explore the potential of MOF-based theranostics for multimodal imaging and drug delivery, Lin et al designed carbon dots embedded MOF@O-carboxymethyl chitosan nanoparticles. 92 The use of O-carboxymethyl chitosan in fabricating the particles provided pH-responsive release of doxorubicin. The developed system could be used for dualimaging including fluorescence and T 2 MRI.…”
Section: Polysaccharide-based Theranosticsmentioning
confidence: 99%
“…The developed nanocomposite acted as a robust theranostic system exhibiting controlled release of both curcumin and 5-FU along with enhanced T 2 MRI contrast in cancer cells. To further explore the potential of MOF-based theranostics for multimodal imaging and drug delivery, Lin et al designed carbon dots embedded MOF@O-carboxymethyl chitosan nanoparticles . The use of O -carboxymethyl chitosan in fabricating the particles provided pH-responsive release of doxorubicin.…”
Section: Polysaccharide-based Theranosticsmentioning
confidence: 99%